VIEWING SOCIAL ISSUES THROUGH CONTEMPORARY FILMS AND BOOKS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the significant role contemporary films and books play in addressing and reflecting upon social issues. It highlights how storytelling, through diverse characters and narratives, provides a platform for examining issues such as racism, gender inequality, mental health, and economic disparity. By humanizing complex social problems, these works foster empathy and spark crucial conversations, bridging the gap between awareness and action.The article also discusses the rise of marginalized voices in literature and film, emphasizing the importance of authentic representation while acknowledging the challenges of commercial interests and stereotypes. Ultimately, it argues that contemporary media serves not only as a mirror to society but also as a tool for social change, inspiring a deeper understanding of the world and motivating a more compassionate, informed approach to addressing the issues we face.